1998
DOI: 10.1002/(sici)1098-2302(199803)32:2<69::aid-dev1>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of long-term memory over the first year-and-a-half of life

Abstract: This research documents the development of long‐term memory in human infants from 2 months through the end of the first year‐and‐a‐half of life. In the initial study phase, we trained 6‐ to 18‐month‐old human infants in an operant task and tested them after increasing delays until they exhibited no retention for 2 successive weeks. In the second phase, their data were combined with data previously obtained from 2‐ to 6‐month‐olds in an equivalent task. The resulting function revealed that the duration of reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 56 publications
5
89
0
Order By: Relevance
“…Hsu (2010) examined how long 6-, 9-, 12-, 15-, and 18-month-old infants retained a memory for an operant task, equivalent to the mobile paradigm, when their second session was completed near the end of their time window. Comparing her data with an earlier study that used the same methodology and completed the second session 24 h after the first (Hartshorn et al, 1998a), Hsu (2010) concluded that for 6-month-old infants completing the second session near the end of the time window resulted in better retention, but for the 9- to 18-month-old infants completing the second session near the end of the time window lead to worse retention than a 24 h space. It is important to note that the 9- to 18-month-old infants successfully retrieved their memory in the second session; thus if Hsu’s (2010) conclusions are correct this calls into question the assumption that more difficult retrievals are always better as suggested by some accounts of the spacing effect (e.g., Bjork and Bjork, 1992; Delaney et al, 2010).…”
Section: The Spacing Effect In Skill-related Tasksmentioning
confidence: 91%
“…Hsu (2010) examined how long 6-, 9-, 12-, 15-, and 18-month-old infants retained a memory for an operant task, equivalent to the mobile paradigm, when their second session was completed near the end of their time window. Comparing her data with an earlier study that used the same methodology and completed the second session 24 h after the first (Hartshorn et al, 1998a), Hsu (2010) concluded that for 6-month-old infants completing the second session near the end of the time window resulted in better retention, but for the 9- to 18-month-old infants completing the second session near the end of the time window lead to worse retention than a 24 h space. It is important to note that the 9- to 18-month-old infants successfully retrieved their memory in the second session; thus if Hsu’s (2010) conclusions are correct this calls into question the assumption that more difficult retrievals are always better as suggested by some accounts of the spacing effect (e.g., Bjork and Bjork, 1992; Delaney et al, 2010).…”
Section: The Spacing Effect In Skill-related Tasksmentioning
confidence: 91%
“…Rovee-Collier and colleagues have investigated infants’ memory retention from 2 to 18 months using the operant reinforcement paradigm (Hartshorn et al, 1998). They demonstrated that 2-month-olds show recognition of the mobile after a 1-day delay period, but not longer (Vander Linde et al, 1985).…”
Section: How Long Can Infants Retain a Memory?mentioning
confidence: 99%
“…This task also reveals a 2-week maximum retention delay for 6-month-olds (Hartshorn and Rovee-Collier, 1997). Nine-month-olds recognize the train after a delay of 6 weeks; 12-month-olds after 8 weeks; 15-month-old after 10 weeks; and 18-month-olds after 13 weeks (Hartshorn et al, 1998). …”
Section: How Long Can Infants Retain a Memory?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have established that memory skills are fragile at the end of the first year of life, but become increasingly stable and robust as infants grow (Bauer, 2005; Bauer, Wenner, Dropik, & Wewerka, 2000; Carver & Bauer, 2001; Hartshorn et al, 1998). The main purpose of the present research was to investigate how reminders given during the post-encoding period influence memory performance in 9-month-olds as measured in a deferred imitation paradigm.…”
mentioning
confidence: 99%